Spare Part Transportation Management in High North - Ayele, Yonas Zewdu; Barabadi, Abbas; Markeset, Tore (Port and Ocean Engineering under Arctic Conditions, 2013)
The demanding physical conditions of the Arctic, remote location, and uncertainty regarding the travel time can both heighten the challenges related to transportation of spare part in the region. Managing to get the appropriate path for transportation of spare parts for oil and gas industries in the region, is one of the major and demanding tasks. In this paper we develop the concept of transportation block diagrams (TBD) for possible transportation routes and mode of transportation. In this method each transportation tools (e.g. truck, railway, etc.) is modeled by block and then a route of the transportation can be a series of these blocks. Furthermore, the concept of transportation network is used to calculate the mean time to transportation for each route. The application of the model is demonstrated by a case study for transportation of spare part for Goliat Oil and Gas Field in the Barents Sea, Norway.